Solid‐State Structure of a Bromo(difluoromethylenephosphonato)cuprate – a Key Intermediate for the Synthesis of α, α‐Difluoromethylenephosphonates. Issue 29 (19th July 2017) - Alter, Christian; Neumann, Beate; Stammler, Hans‐Georg; Weber, Lothar; Hoge, Berthold
Abstract: Invited for the cover of this issue is the group of Prof. Dr. Berthold Hoge from Bielefeld University, Germany. The cover image shows the crystal structure of a bromo(difluoromethylenephosphonato)cuprate finally in the spotlight after waiting "backstage" for 28 years. Abstract : Despite the vast amount of work accomplished since 1989, the structure and composition of the reactive copper intermediate had remained unclear for nearly thirty years… Read more about the story behind the cover in the Cover Profile and about the research itself on page 3489 ff(https://doi.org/10.1002/ejic.201700526 ).